Fatores de risco associados às soropositividades para Leishmania spp. E Trypanosoma cruzi em cães no Estado da Paraíba, Brasil - Fernandes, Annielle Regina da Fonseca; Pimenta, Carla Lauise Rodrigues Menezes; Vidal, Ivana Fernandes; Oliveira, Gabriela Capriogli [UNESP]; Sartori, Raissa Saran [UNESP]; Araújo, Raizza Barros; Melo, Márcia Almeida; Langoni, Hélio [UNESP]; Azevedo, Sérgio Santos (FapUNIFESP (SciELO), 2016)
The aim of this survey was to determine the seropositivity and risk factors for Leishmania spp. and Trypanosoma cruzi in dogs in the State of Paraíba, Northeastern Brazil. A total of 1,043 dogs were tested, and the serological diagnoses of Chagas disease (CD) and canine visceral leishmaniasis (CVL) was performed by the indirect fluorescent antibody test (IFAT). Animals that tested seropositive for both diseases (by IFAT) were further subjected to ELISA. Of the 1,043 dogs 81 (7.8%; 95% CI = 6.1-9.4%) tested seropositive for Leishmania spp., while 83 were seropositive for T. cruzi (7.9%; 95% CI = 6.3-9.6%). Simultaneous serological reactions were detected in 49 animals (4.6%; 95% CI= 3.6-6.2%). Semi-domiciled housing (OR = 2.044), free housing (OR = 4.151), and soil (OR = 3.425) and soil/cement (OR = 3.065) environmental conditions were identified as risk factors for CVL seropositivity. The risk factors identified for CD seropositivity were semi-domiciled (OR = 2.353) or free housing (OR = 3.454), and contact with bovine (OR = 2.015). This study revealed the presence of dogs in the Paraíba State seropositive for CVL and CD, suggesting the need for revisiting and intensification of disease control measures through constant monitoring of the canine population.
Risk factors associated with seropositivity for leishmania spp. And trypanosoma Cruzi in dogs in the state of Paraiba, Brazil
Keywords: Dogs; Leishmania infantum; Northeastern region of Brazil; Risk factors; Trypanosoma cruzi